2020
DOI: 10.1016/j.celrep.2020.107697
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Palmitoylation of the Sodium-Calcium Exchanger Modulates Its Structure, Affinity for Lipid-Ordered Domains, and Inhibition by XIP

Abstract: Highlights d NCX1 is dynamically palmitoylated at the cell surface by zDHHC5 and APT1 d Palmitoylation modifies the NCX1 dimer's structure and affinity for lipid rafts d We identify the binding site of the endogenous XIP domain in NCX1's regulatory loop d Palmitoylation modifies NCX1 XIP affinity and hence regulates intracellular Ca

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 62 publications
(88 reference statements)
0
46
0
Order By: Relevance
“…G i α13 is obviously not the sole APT1 substrate. Since we began this project, several additional substrates have been reported: the microtubule-associated protein 6 MAP6 ( 45 ), the CD36 receptor ( 46 ), R-RAS ( 47 ), and the Na/Ca exchanger NCX1 ( 48 ). Last, an unbiased approach recently identified 382 potential APT1 substrates, although these have yet to be validated in vivo ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…G i α13 is obviously not the sole APT1 substrate. Since we began this project, several additional substrates have been reported: the microtubule-associated protein 6 MAP6 ( 45 ), the CD36 receptor ( 46 ), R-RAS ( 47 ), and the Na/Ca exchanger NCX1 ( 48 ). Last, an unbiased approach recently identified 382 potential APT1 substrates, although these have yet to be validated in vivo ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…It will be of particular interest to study the kinetics of S-acylation in relation to subsequent molecular and cellular events. For example, by using fluorescence resonance energy transfer (FRET) in live cells, it was recently found that the dynamic palmitoylation of sodium-calcium exchanger 1 (NCX1) leads to rearrangement of the f-loop region and regulate its dimerization ( Gök et al, 2020 ). These acylation-induced changes are key in recruiting the exchange inhibitory peptide and mediating Ca 2+ influx.…”
Section: Functional Outcomes Of S-acylationmentioning
confidence: 99%
“…Similarly, the S-acyl chains (either at cysteine-166 or other sites in the channel) might also mediate specific interactions with membrane lipids, which could alter membrane micro-localization, and this will be interesting to explore in future work. Effects of S-acylation on protein interaction with cholesterol-rich lipid-ordered domains at the plasma membrane have been documented for a number of transmembrane proteins, including the sodium–calcium exchanger NCX1, which displays S-acylation-dependent accumulation in lipid-ordered domains that is linked to transporter function [ 32 ].…”
Section: Insulin Secretionmentioning
confidence: 99%
“…Thus, it will be interesting to examine if S-acylation increases the preference of the insulin receptor for a lipid-ordered membrane environment and if this contributes to caveolar association [ 90 ]. As a starting point, the relative association of wild-type and S-acylation-null receptor with ordered and disordered domains in giant plasma membrane vesicles could be assessed [ 32 ].
Figure 3 S-acylation of components of the insulin signalling and IRV exocytosis pathways.
…”
Section: Insulin Signalling and Glut4 Vesicle Exocytosismentioning
confidence: 99%